The relations of vascular endothelial growth factor–C and lymph node metastasis in breast cancer patients - Mungan, İbrahim; Doğru, Osman; Aygen, Erhan; Dağlı, Adile Ferda (Journal of Surgery and Medicine, 2019)
Aim: Breast cancer (BC) is the 2nd most common cancer worldwide and most of the cases are sporadic. BC chooses mainly the lymphatic system and axillary lymph nodes (LN) are frequently involved. Lymph node metastasis (LNM) is driven by tumor-derived lymphangiogenic growth factors, especially vascular endothelial growth factor (VEGF) family. Higher serum levels of VEGF-C have been detected in cases of BC. In the present study, we aim to investigate the expression pattern of VEGF-C in tumor specimens and the relation of VEGF-C expression with LNM by immunohistochemistry. Methods: In this clinical, cross-sectional study, paraffin-embedded specimens were obtained from 16 female patients who had primary invasive ductal breast cancer and received surgical treatment between April 2006 and March 2007. BC tissue sections were stained with VEGF-C antibody and evaluated according to the severity and intensity of the staining. Statistical analysis was performed using SPSS version 15.0 for Windows and in all analyses, a ‘p’ value less than 0.05 was considered statistically significant and comparisons were 2-tailed. Results: The average age at the time of diagnosis was 50 years (range: 24-82 years). In the present study, on the basis of SI and SS VEGF-C expression did not show statistically significant correlation with LNM, while calculated IRS - as a variable- was correlated with LNM. The grade of the tumor correlated neither with the VEGF-C expression nor with lymph node metastasis (p>0.05). Conclusions: It is interesting that the correlation with VEGF-C IRS score and axillary lymph node level was found significant statistically. In the current study, we demonstrated the VEGF-C relation with LNM via IHC staining in tumoral samples of BC patients.